Broadcasting politics in Japan : - Krauss, Ellis S. (Cornell University Press, 2000)
This book introduction the broadcasting of politics, the politics of broadcasting, organization and Its environment, leadership and politics, occupational roles and politics, new media strategies and organizational change....